Thomas Perkins house, Mount Vernon Street, ca. 1855-1865 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking northwest of the rear of building at the corner of Mount Vernon Street and Joy Street. This is a multistory brick dwelling. View is of the area behind the structure, several people are standing and some are looking fromm upper story windows. 11 1/4 x 10 Photographs